ANTIOXIDANT ACTIVITY OF TEGINING GANANG (Senna hirsuta L) LEAF EXTRACT USING DPPH METHOD - Hendriyani, Irmatika; Maulida, Meri Kartika; Wahid, Abdul Rahman; Khairi, Widayatul; Sugara, Taufan Hari (Universitas Muhammadiyah Ahmad Dahlan Cirebon, 2025)
Tegining ganang (Senna hirsuta L) is a commodity plants on Lombok Island and is traditionally used to treat minor wounds, severe wounds, and skin infections. This study aimed to evaluate the antibacterial and antioxidant activities of ethanol, ethyl acetate, and n-hexane extracts of Tegining ganang leaves against Staphylococcus aureus and Escherichia coli using the DPPH method. The results showed that the ethyl acetate extract exhibited the highest antibacterial activity. Escherichia coli with an inhibition zone of 8.16 mm. For Staphylococcus aureus, the inhibition zone was 1.16 mm. However, all three extracts demonstrated weak antifungal activity. Phytochemical screening revealed the presence of alkaloids and flavonoids in all the extracts. Additionally, the ethanol and ethyl acetate extracts contained phenolic compounds and tannins, which were absent in the n-hexane extract. In the antioxidant activity assay, the 96% ethanol extract demonstrated excellent antioxidant activity with average absorbance values of 0,496 ± 0,018 at 10 ppm, 0,438 ± 0,008 at 20 ppm, 0,357 ± 0,003 at 30 ppm, and 0,326 ± 0,002 at 40 ppm, resulting in an IC?? value of 16,67 ppm. The ethyl acetate extract had an absorbance of 0,537 ± 0,010 at 10 ppm, 0,487 ± 0,002 at 20 ppm, 0,443 ± 0,011 at 30 ppm, 0,392 ± 0,003 at 40 ppm, and 0,383 ± 0,005 at 50 ppm, with an IC?? of 28,50 ppm ...